The Carnival of Custom: Land Dives, Millenarian Parades and Other Spectacular Ritualizations in Vanuatu. - Tabani, Marc (Oceania, 2010)
This paper deals with the aestheticization and commoditization of culture in specific grand rituals held in Vanuatu. Through political, commercial and juridical processes, the traditional referent of these neo-ritualizations has been replaced by a celebration of the kastom theme itself; the official value of a regional, national, and global cultural heritage. The examination of two iconic rituals, the Nagol land dive on Pentecost island and the 15th February annual commemoration of John Frum on Tanna island, reveals them as similarly invoking a Christian and colonially inspired reverence in their idealization of an ancestral past. Nevertheless, the increasing monetarization of village communities through the global promotion of kastom spectacles by media and for touristic purposes is ever more frequently considered locally as a factor of inequality or division.